Desarrollo de prácticas de automatización a través de un módulo didáctico con el PLC S7-1200 para el control automático de llenado de un tanque - Flores Zamora, Guillermo Gabriel (2017)
Currently programming is the main element of the automatic systems in industries, companies and factories through which it has been fundamental base in the development and advance of the production, providing a greater security. With this project we aim to increase theoretical-practical knowledge, achieving better progress in developing the different didactic practical activities with students, allowing the educational community to interact with the medium in an easy and meaningful way. The lack of a programming system is the idea of designing a didactic module with the PLC S7-1200, this will allow students to complement their programming knowledge of the PLC, through their respective programs and necessary equipment used in the industries companies and factories that allows us to control the water level to avoid spillage and problems, in production due to automation the results are positive and generate a clearer knowledge for society. The present research will be carried out through the use of experimental design and explanatory research, which will allow the development of a didactic module for the automatic control of filling of a tank. This didactic module will be a method of study for the correct and efficient learning of the students, in order that the students have a significant learning.